2015
DOI: 10.1177/0301006615594266
|View full text |Cite
|
Sign up to set email alerts
|

Are You Suggesting That’s My Hand? The Relation Between Hypnotic Suggestibility and the Rubber Hand Illusion

Abstract: Abstract. Hypnotic suggestibility (HS) is the ability to respond automatically to suggestions and to experience alterations in perception and behaviour. Hypnotically suggestible participants are also better able to focus and sustain their attention on an experimental stimulus. The present study explores the relation between HS and susceptibility to the rubber hand illusion (RHI). Based on previous research with visual illusions, it was predicted that higher HS would lead to a stronger RHI illusion. Two behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 72 publications
(144 reference statements)
4
43
2
Order By: Relevance
“…Our observations contrast with a recent study [11] in which proprioceptive drift was found to positively correlate with another type of suggestibility—hypnotic suggestibility (i.e., the ability to experience suggested sensations, emotions, and thoughts during hypnotic induction) [11]. Sensory and hypnotic suggestibility involve different cognitive processes, however: the former requires an imagery ability related to a non-existent, but suggested, sensation [23], whereas the latter also involves heightened attentional focus and the ability to ignore sources of interference during hypnotic induction [11].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our observations contrast with a recent study [11] in which proprioceptive drift was found to positively correlate with another type of suggestibility—hypnotic suggestibility (i.e., the ability to experience suggested sensations, emotions, and thoughts during hypnotic induction) [11]. Sensory and hypnotic suggestibility involve different cognitive processes, however: the former requires an imagery ability related to a non-existent, but suggested, sensation [23], whereas the latter also involves heightened attentional focus and the ability to ignore sources of interference during hypnotic induction [11].…”
Section: Discussioncontrasting
confidence: 99%
“…One could argue that highly suggestible individuals are generally more compliant and tend to rate questionnaire statements higher [11]. Although we cannot completely exclude this factor, we believe that compliance alone cannot explain our findings.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations